Politics of Inner Place - Van Harten, Gus (UnderCurrents: Journal of Critical Environmental Studies, 1995)
What is place? A niche ... a spot... a situation in time. Identity. Beliefs. A quiltwork of designs, a web of choices, a muster of visits co ocher places, and a need to dwell in one's own. [...]